Resolving the Incomplete Charging Behavior of Redox-Mediated Li-O2 Batteries via Sustainable Protection of Li Metal Anode - Kim, Hun; Min, Kyeong-Jun; Jeong, Min-Gi; Jung, Hun-Gi; Sun, Yang-Kook (American Chemical Society, 2022)
Lithium-oxygen batteries (LOBs) have attracted worldwide attention due to their high specific energy. However, the poor rechargeability and cycling stability of LOBs hinders their practical use in applications. Here, we explore the incomplete charging behavior of redox-mediated LOBs operated at a feasible capacity for a practical level (3.25 mAh cm-2) and resolve it using a sustainable lithium protection strategy. The incomplete charging behavior, promoted by self-discharge of redox mediators (RMs), hampers the reversible cycling of LOBs, which was investigated through multiangle in situ and ex situ analyses. Meanwhile, the proposed lithium protection strategy, introducing an inorganic/ organic hybrid artificial composite layer with a preformed stable interface between the lithium metal and the composite layer, enhances the stability of the lithium metal anode during the prolonged cycling by preventing the chemical/electrochemical interactions of RMs on the lithium metal surface, thus improving the overall rechargeability of LOBs. This work provides guidelines for the effective use of RMs with an adequate lithium protection strategy to achieve sustainable cycling of LOBs, creating a feasible approach for the practical use of LOBs with high areal capacity.